Preparation and Application of Nanosensor in Safeguarding Heparin Supply Chain. (August 2020) - Bi, Yiling; Le, Khoi Dang; Ramamoorthy, Gurusankar; Kuberan, Balagurunathan
Heparin has been in clinical use as an anticoagulant for the last eight decades and used worldwide in more than 100 million medical procedures every year. This lifesaving drug is predominantly obtained from 700 million pig intestines or bovine organs through millions of small and medium-sized slaughterhouses. However, the preparations from animal sources have raised many safety concerns, including the contamination of heparin with potential pathogens, proteins, and other impurities. In fact, contaminated heparin preparations caused 149 deaths in several countries, including the United States, Germany, and Japan in 2008, highlighting the need for implementing sensitive and simple analytical techniques to monitor and safeguard the heparin supply chain. The contaminant responsible for the adverse effects in 2008 was identified as oversulfated chondroitin sulfate (OSCS). We have developed a very sensitive, facile method of detecting OSCS in heparin lots using a nanosensor, a gold nanoparticle–heparin dye conjugate. The sensor is an excellent substrate for heparitinase enzyme, which cleaves the heparin polymer into smaller disaccharide fragments, and therefore facilitates recovery of fluorescence from the dye upon heparitinase treatment. However, the presence of OSCS results in diminished fluorescence recovery from the nanosensor upon heparitinase treatment, because OSCS inhibits the enzyme. The newly designed nanosensor can detect as low as 1 × 10 –9 % (w/w) OSCS, making it the most sensitive tool available to date for the detection of trace amounts of OSCS in pharmaceutical heparins. In this report, we describe a simple methodology for the preparation of nanosensor and its application in the detection of OSCS contaminants.